Improving Mathematics Learning Outcomes on the Subject of Place Value Numbers Using Number Boxes in Class I Students - Sumiyatun, Sumiyatun (Universitas Sebelas Maret, 2022)
This study aims to improve the understanding of the concept of place value in grade 1 students using the number box media at SDN Banyuagung II Surakarta. This study uses qualitative research with classroom action research. The data source is class 1 of SDN Banyuagung II Surakarta. Data collection techniques are observation, interviews, tests and documentation. This research was conducted in 2 cycles and each cycle there were 2 meetings. The application of number box media is able to increase the understanding of the place value concept of tens and ones in grade 1 students at SDN Banyuagung II Surakarta. This can be seen from the results of student learning in the pre-cycle the average student score of 55 increased to 65 in cycle I and 80 in cycle II with the percentage of completeness from 37% in pre-cycle to 62% in cycle I and 81% in cycle II.